2017
DOI: 10.1371/journal.pone.0170056
|View full text |Cite
|
Sign up to set email alerts
|

Review and Analysis of Publication Trends over Three Decades in Three High Impact Medicine Journals

Abstract: ContextOver the past three decades, industry sponsored research expanded in the United States. Financial incentives can lead to potential conflicts of interest (COI) resulting in underreporting of negative study results.ObjectiveWe hypothesized that over the three decades, there would be an increase in: a) reporting of conflict of interest and source of funding; b) percentage of randomized control trials c) number of patients per study and d) industry funding.Data sources and Study SelectionOriginal articles p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…Furthermore, scientific productivity in academia is traditionally assessed based on the number of publications. Consequently, new scientific journals appear even if some of them are classified as 'predatory' (lacking integrity in the publishing process usually without an accurate peer review process, fake impact factor or editorial team, issues that could be difficult to detect) and the number of published scientific articles increases annually [1][2][3]. The retraction of an article is used to alert scientists to serious problems identified with a published article and follows the Committee on Publication Ethics retraction guideline [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, scientific productivity in academia is traditionally assessed based on the number of publications. Consequently, new scientific journals appear even if some of them are classified as 'predatory' (lacking integrity in the publishing process usually without an accurate peer review process, fake impact factor or editorial team, issues that could be difficult to detect) and the number of published scientific articles increases annually [1][2][3]. The retraction of an article is used to alert scientists to serious problems identified with a published article and follows the Committee on Publication Ethics retraction guideline [4].…”
Section: Introductionmentioning
confidence: 99%
“…Conflicts of interest (CoIs) were defined as "a set of circumstances that creates a risk that professional judgment or actions regarding a primary interest will be unduly influenced by a secondary interest" [13]. The transparency of CoI has become increasingly ubiquitous for primary sources [14] including clinical trials [15], undergraduate medical education [16], continuing medical education [17], point of care computerized sources [18], meta-analyses [19], and clinical practice guidelines [20]. The US Physician Payments Sunshine Act of 2010 required that all compensation (≥$10) to doctors of medicine, osteopathy, dentistry, dental surgery, podiatry, optometry, and chiropractic medicine (i.e., PharmDs, PhDs, PAs, and NPs were not covered although this subsequently changed for PAs and NPs) from manufacturers of drugs and medical devices be reported to the Centers for Medicare and Medicaid Services (CMS), and made available on its public website.…”
Section: Introductionmentioning
confidence: 99%
“…While no study reported these in 1997, the large majority did so in 2017. Ivanov et al 20 concluded that improved reporting of conflicts of interest and clarity around financial sponsorship represent a positive step forward. Journals now require authors to report conflicts of interests.…”
Section: Discussionmentioning
confidence: 99%